Sorption and Degradation Capacity of Natural Estrogens in Freshwater Environmental System in Japan - Reni Desmiarti; Fu-Sheng Li (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
The sorption and the degradation capacity of natural estrogens in freshwater environmental system in Japan were performed. Batch experiments were examined in water-sediment suspensions using six layers of sediment under aerobic and anaerobic conditions. The results indicated that the water-sediment partition coefficient of E1 (KdE1) was higher than E2 (KdE2). The degradation rate of E1 (kE1) was smaller than E2 (kE2). Under aerobic and anaerobic conditions, E1 was formed from E2. The degradation rate of E2 (kE2) from the surface to bottom of sediment layers was estimated fell in the range from 0.114 to 0.026 h-1 and 0.05 to 0.014 h-1 under aerobic and anaerobic conditions, respectively.